Answer:
1. D
2. A
Step-by-step explanation:
Q1. Kerry is simplifying [tex]5\cdot 10^{-3}[/tex]
By the definition of negative powers,
[tex]a^{-n}=\dfrac{1}{a^n}[/tex]
Hence,
[tex]10^{-3}=\dfrac{1}{10^3}[/tex]
So, the first step in simplifying the expression is
[tex]5\cdot 10^{-3}=5\cdot \dfrac{1}{10^3}[/tex]
Q2. Given the expression
[tex]\dfrac{8}{10^{-2}}[/tex]
First, use the definition of negative powers:
[tex]10^{-2}=\dfrac{1}{10^2}[/tex]
Thus,
[tex]\dfrac{8}{10^-2}=\dfrac{8}{\frac{1}{10^2}}=8\cdot 10^2=8\cdot 100=800[/tex]